Discursive constructions of the new water legislation in Ecuador - Zapata, Alexander (2017)
Based on the concept of «law discourse content» developed by Óscar Correas, this article examines the more outstanding and controversial issues of the new water regulation framework in Ecuador, with emphasis on the «Ley Orgánica de Recursos Hídricos, Usos y Aprovechamiento del Agua», in force since second half 2014, andidentifying the tensions between the discursive constructions that frame the new regulation. This leads us to the following conclusion: the law reveals a political conception on water management by the «Citizen Revolution» which, from the vertical control of the state apparatus, encourages a capitalist modernization of the economy seeking to support and expand a rentier use of water.